Adult Attachment Orientations and Social Networking Site Addiction: The Mediating Effects of Online Social Support and the Fear of Missing Out - Liu, Chang; Ma, Jian-Ling (Frontiers in Psychology, 2019)
Evidence supports predictive roles of adult attachment styles for the maintenance of social networking site addiction, but the underlying mechanisms are mostly unknown. Based on attachment theory, this study explored whether online social support and the fear of missing out mediated the relationship between insecure attachment styles and social networking site addiction among 463 college students in China. A questionnaire was used to collect data using the Experience in Close Relationship Scale–Short Form, online social support scale, fear of missing out scale, and Chinese Social Media Addiction Scale. The results showed that online social support and fear of missing out mediated the relationship between anxious attachment and social networking site addiction in parallel paths and serially, and online social support negatively mediated the relationship between avoidant attachment and social networking site addiction. Theoretically, the present study contributes to the field by showing how insecure attachment styles are linked to SNS addiction. Practically, these findings could aid in future studies on SNS addiction prevention and interventions. Limitations of the present study were discussed.